JAK/STAT signaling is involved in air sac primordium development of Drosophila melanogaster. Issue 7 (20th March 2019) - Powers, Nathan; Srivastava, Ajay
Abstract : The dorsal thoracic air sacs in fruit flies ( Drosophila melanogaster ) are functionally and developmentally comparable to human lungs. The progenitors of these structures, air sac primordia (ASPs), invasively propagate into wing imaginal disks, employing mechanisms similar to those that promote metastasis in malignant tumors. We investigated whether Janus kinase/signal transducer and activator of transcription JAK/STAT signaling plays a role in the directed morphogenesis of ASPs. We find that JAK/STAT signaling occurs in ASP tip cells and misexpression of core components in the JAK/STAT signaling cascade significantly impedes ASP development. We further identify Upd2 as an activating ligand for JAK/STAT activity in the ASP. Together, these data constitute a considerable step forward in understanding the role of JAK/STAT signaling in ASPs and similar structures in mammalian models. Abstract :